Social Complaint Application (International Journal of Engineering and Computer Science, 2017)
Now-a-days we all have been so unsatisfied with a social service provider like MSEB OR Water supply company that we felt the need to register our grievances with the offending company. Most of the time complaints go unheard, unanswered and unresolved usually because the company is too large to have to worry about one little complaint from one single customer. And this application is here to help. We are aiming to create a mobile application which deals with social complaints and their recovery. This app will be providing the facility of lodging complaints on a mobile phone and track that complaint till its resolved. The various types of complaints could be road repairing, cleaning, emergency services (E.g. Fire, Ambulance)etc. Our idea is to create a mobile application which can help you out with registering the complaints online without the need to have a laptop or desktop with you. Just one click and you can lodge a complaint anywhere, anytime. Our objective of creating this app is to make complaints easier to co-ordinate, monitor and resolve.